Effect of Remote Peer-Counsellor- delivered Behavioral Activation and Peer-support for Antenatal Depression on Gestational Age at Delivery: a single-blind, randomized control trial - Kathleen H. Chaput; Makayla Freeman; Carly McMorris; Amy Metcalfe; Emily E. Cameron; James Jung; Suzanne Tough; Laurel M. Hicks; Sona Dimidjian; Lianne M. Tomfohr-Madsen (Trials, 2023)
Abstract Background Antenatal depression (AD) is the most common complication of pregnancy in developed countries and increases the risk of preterm birth (PTB). Many pregnant individuals with AD do not obtain treatment due in part to risks associated with antidepressant medications, the expense and wait times for psychological services, and perceived stigma. Accessible and timely treatment of antenatal depression is crucial to minimize foetal impacts and associated long-term child health outcomes. Previous studies show that behavioural activation and peer support are promising avenues of treatment for perinatal depression. Additionally, remote and paraprofessional counselling interventions show promise as more accessible, sustainable, and cost-effective treatment avenues than traditional psychological services. The primary aim of this trial is to test the effectiveness of a remote, behavioural activation and peer support intervention, administered by trained peer para-professionals, for increasing gestational age at delivery among those with antenatal depression. The secondary aims are to evaluate the effectiveness for treating AD prior to delivery, with persistence into the postpartum; improving anxiety symptoms; and improving parenting self-efficacy compared to controls. Methods A two-arm, single-blinded, parallel groups randomized controlled trial (RCT) with repeated measures will be conducted. Participants scoring >10 on the Edinburgh Postnatal Depression Scale will be recruited from the larger P3 cohort and invited to enroll. Assessments will be conducted prior to 27 weeks’ gestation at trial intake (T1), post-intervention, prior to delivery (T2), 5–6 months postpartum (T3), and 11–12 months postpartum (T4) and will include self-report questionnaires and linked medical records. Discussion Our remote, peer paraprofessional-delivered behavioural activation plus peer support intervention has the potential to successfully reduce symptoms of AD, which may in turn decrease the risk of PTB and subsequent health impacts. The current trial builds on previous findings and uses a patient-oriented approach to address priorities for patient care and to provide a cost-effective, accessible, and evidence-based treatment to pregnant individuals with AD. Trial registration International Standard Randomised Controlled Trial Number (ISRCTN) registry (ISRCTN51098220) ISRCTN51098220. Registered on April 7, 2022.